2016
DOI: 10.15537/smj.2016.12.15972
|View full text |Cite
|
Sign up to set email alerts
|

Roles of nucleolin

Abstract: Nucleolin, a multifunctional protein distributed in the nucleolus, participates in many modulations including rDNA transcription, RNA metabolism, and ribosome assembly. Nucleolin is also found in the cytoplasm and on the cell membrane, and surface nucleolin can bind to various ligands to affect many physiological functions. The expression and localization of nucleolin is often abnormal in cancers, as the differential distribution of nucleolin in cancer can influence the carcinogenesis, proliferation, survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 45 publications
(50 reference statements)
1
38
0
3
Order By: Relevance
“…When nucleolar stress occurs, the levels of these three proteins increase and the proteins translocate from the nucleus to the cytoplasm ( 12 , 13 ). Nucleolin is the major nucleolar protein of exponentially growing eukaryotic cells, and participates in many modulations including rDNA transcription, RNA metabolism, and ribosome assembly ( 14 ). Nucleophosmin is a highly and ubiquitously expressed protein, and plays crucial roles in ribosome maturation and export, centrosome duplication and cell cycle progression ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…When nucleolar stress occurs, the levels of these three proteins increase and the proteins translocate from the nucleus to the cytoplasm ( 12 , 13 ). Nucleolin is the major nucleolar protein of exponentially growing eukaryotic cells, and participates in many modulations including rDNA transcription, RNA metabolism, and ribosome assembly ( 14 ). Nucleophosmin is a highly and ubiquitously expressed protein, and plays crucial roles in ribosome maturation and export, centrosome duplication and cell cycle progression ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, nucleolin stabilizes the mRNA of anti-apoptotic protein bcl-2 [ 53 ]. Recent studies have proposed that nucleolin is a novel target for anticancer therapy as demonstrated by the effects of antagonistic molecules [ 33 , 54 , 55 ]. Nucleolin is a multifunctional protein that is mainly found in the nucleolus, but it is also observed in the nucleoplasm and cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-targeting ligand in the TDDS is a DNA aptamer (AS1411) that and can bind with nucleolin, which is expressed on the cell surface of colon cancer. 24 DTX is an FDA-approved broad-spectrum anticancer agent that is more potent than paclitaxel. 25 , 26 We now report that Apt-NPs-DTX is more efficacious against colon cancer cells vs non-targeted drug delivery system.…”
Section: Introductionmentioning
confidence: 99%